Cotton Cost-Return Budget in South Central and Southeast Kansas - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Shoup, Douglas; Duncan, Stewart R.; Haag, Lucas (My University, 2014)
This publication projects a budget that reflects expected income and costs based on production of cotton in south central and southeast Kansas.
MF939_2014_02
Keywords: MF939; Economics; Crops; MF